فعالية الوسائط التعليمية القائمة على الفيديو الكرتونية في تحسين مهارة الكلام لدى طالبات الصف التاسع في معهد دار الأبرار بوني - Nurfitri Sari; Agussalim Beddu Malla; Bisyri Abd Karim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to find out the effectiveness of cartoon video as alearning media to improve maharah al-kalam (Arabic speaking skill) of femalestudents at Pesantren Darul Abrar. This study uses a quantitative approachwith a quasi-experimental design. The sample consists of two groups: theexperimental group that used cartoon videos and the control group that usedtraditional learning methods. Data was collected using speaking tests beforeand after the treatment (pre-test and post-test).The validity test shows thatmost items have an r-count higher than the r-table (0.444) with significance <0.05, so the instrument is valid. One item is below the r-table value but stillhas acceptable significance. The reliability test shows a Cronbach’s Alphavalue of 0.800, which means the instrument is highly reliable.The data isnormally distributed (sig. = 0.200) and homogeneous (sig. = 0.200), so itmeets the basic assumptions for regression analysis. The t-test result showsthat religiosity has a significant effect on positive aggressiveness, which inthis context means speaking confidence, with a coefficient value of 0.371 andsignificance of 0.002. This means cartoon videos are effective as learningmedia to improve maharah al-kalam, especially when connected to Islamicvalues that are already present in the pesantren environment.